2021
DOI: 10.2174/1871520621666210112121051
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Cytotoxic and Apoptotic Effect of Resveratrol and Naringenin on Y79 Retinoblastoma Cell Line

Abstract: Background: Resveratrol is a phenolic natural product which is found in red grapes also in Japanese knotweed root (Polygonum cuspidatum). Naringenin is one of the flavonoid compounds found in landing grape and other citrus fruits. Both agents exert antioxidant and anti-inflammatory properties. Objective: In this study, we investigated the effect of Resveratrol and Naringenin in an in vitro model of retinoblastoma of the eye. Method: XTT and trypan blue assays used to evaluate the anti-proliferative/cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Sareen et al demonstrated that due to RSV, the growth of the retinoblastoma cell line in a time- and dose-dependent manner is inhibited, while cycle S-phase cell arrest and apoptosis are promoted [ 106 ]. Other researchers reached similar results [ 107 ].…”
Section: Resveratrol In Eye Diseasessupporting
confidence: 81%
See 1 more Smart Citation
“…Sareen et al demonstrated that due to RSV, the growth of the retinoblastoma cell line in a time- and dose-dependent manner is inhibited, while cycle S-phase cell arrest and apoptosis are promoted [ 106 ]. Other researchers reached similar results [ 107 ].…”
Section: Resveratrol In Eye Diseasessupporting
confidence: 81%
“…RSV treatment results in death and regression of neoplastic cells [ 105 , 106 , 107 ]. RSV suppresses the growth of uveal melanoma through early mitochondrial dysfunction and caspase-3 activation [ 105 ].…”
Section: Resveratrol In Eye Diseasesmentioning
confidence: 99%